Managing Liberalization and Globalization in Rural China: Trends in Rural Labour Allocation, Income and Inequality - Dong, Xiao-Yuan; Bowles, Paul; Chang, Hongqin (Global Labour Journal, 2009)
China’s integration into the global economy, while rapid, has been managed as part of a wider liberalization process. The structural changes in the rural economy arising from these twin processes have led to widening intra-rural inequalities. To address these, the central leadership has, in Polanyian manner, moved to counter some of the adverse effects of liberalization and globalization. We discuss this dynamic as it has affected rural China. We analyze results from a national data set covering the period 1991-2006 to assess the extent to which the state has been successful in protecting society from the advance of market forces. We find positive outcomes in terms of real earnings growth and poverty reduction but negative outcomes in terms of the rise in open unemployment and in terms of increasing intra-rural income inequality, although this was noticeably more pronounced in the 1991-2000 period than in the 2000-2006 period when more active government redistributive mechanisms were in place.
Keywords: globalization; income inequality; labor studies; labour allocation; labour studies; liberalization; rural China

Globalization(s) and Labour in China and India: Introductory Reflections - Harriss, John (Global Labour Journal, 2009)
I find it helpful to view the events of the past twenty years or so in a Polanyian frame, and specifically to enquire as to the working out of the ‘double movement’ as the attempt has been made, in both China and India, albeit partially, to shift towards the self-regulating market.
Keywords: China; India; double movement; globalization; labor; labour

Performing economy differently: Exploring economic personhood and local economic diversity - McKay, Deirdre (The Australian Journal of Anthropology, 2009)
Many popular conceptions of economy now delimit what counts as the ‘real’ economy by capitalist enterprises, market transactions and wage labour. Anthropologists describe such ideas of economy as abstract, dis-embedded (Polanyi 1957a, b) or virtual (Carrier and Miller 1998), arguing that these conceptions are not adequate to the empirical realities of lived experience. Beyond anthropology, there is a growing literature that theorises the ways academic accounts have themselves brought a dis-embedded or virtual version of economy into being (Mitchell 2002, 2008; Callon 2005; Callon and Caliskan 2005; Latour 2005; Gibson-Graham 2006). Scholars advocating a performative approach argue that academic notions of economy are not simply descriptive of empirical realities, but actively shape those realities, giving form to the ways that a ‘real’ economy emerges from particular socio-cultural fields. In the context of applied development anthropology, a performative reading of economy offers a helpful platform for applied research directed towards diversifying local economic understandings and practices. This paper explores the implications of performing economy differently through reflections on an action research project undertaken in the Philippines. Here, a performative approach recreated economy as a space of decision that demands active, ethical choices (Gibson-Graham 2006) and supported relational, rather than individuated, models of economic personhood.
Keywords: action research; disembeddedness; economic anthropology; performative approach

Industrial Policy in the United States: A Neo-Polanyian Interpretation - Schrank, Andrew; Whitford, Josh (Politics & Society, 2009)
The conventional wisdom holds that U.S. political institutions are inhospitable to industrial policy. The authors call the conventional wisdom into question by making four claims: (1) the activities targeted by industrial policy are increasingly governed by decentralized production networks rather than markets or hierarchies, (2) "network failures" are therefore no less threatening to industrial dynamism than market or organizational failures, (3) the spatial and organizational decentralization of production have simultaneously increased the demand and broadened the support for American industrial policy, and (4) political decentralization is therefore likely to improve the functioning of industrial policies designed to combat network failures.
Keywords: United States; decentralization in government; economic activity; federalism; governance; industrial organization (economic theory); industrial policy; networks; production (economic theory)

Political Cycles, Political Institutions and Public Expenditure in India, 1980-2000 - Sáez, Lawrence; Sinha, Aseema (British Journal of Political Science, 2009)
In Western democracies it is held that parties and their positions affect how politicians choose to make public expenditure and investment. This article examines the public policy choices of politicians in India, a large well-established democracy with remarkable subnational variation. Public expenditure, from education and health to agriculture and irrigation, is analysed. Counterintuitive findings - that election timing and political factors play a strong role in the subnational states, and that party competition increases investment in education - are explained by highlighting the role economic and political uncertainty plays in politicians' choices. Building a 'Polanyi' argument enhanced by a supply-side mechanism highlights the importance of compensation and insurance and the imperatives of political stability for subnational politicians, who attempt to maximize re-election chances in an uncertain environment.
Keywords: India; budget - law and legislation; elections; government purchasing; government spending policy; policy sciences; public administration; public spending; representative government; tax and expenditure limitations

Polanyi in Brussels: Supranational Institutions and the Transnational Embedding of Markets - Caporaso, James A.; Tarrow, Sidney (International Organization, 2009)
AbstractMany have argued that the success of European integration is predicated on reinforcing market structures and some have gone further to state that the creation of a transnational market results in a decoupling of markets from their national political and social frameworks, thus threatening to unravel historical social bargains. Drawing on the work of Karl Polanyi and John Ruggie and using their insights regarding the social embedding of markets, we dissent from this view by examining how the European Court of Justice (ECJ) has handled a key sector of the emerging European market—labor mobility. We argue that rather than disembedding markets, decisions of the ECJ—just as Polanyi and Ruggie would have predicted—activate new social and political arrangements. We find evidence for the development of a new legal and political structure, largely inspired by the Court but also imbricated in European Union legislation, at the regional level.
Keywords: European Court of Justice; embedded markets

No hay ganancia en la milpa: the agrarian question, food sovereignty, and the on-farm conservation of agrobiodiversity in the Guatemalan highlands - Isakson, S. Ryan (Journal of Peasant Studies, 2009)
Although they receive little recognition for their contribution, peasant farmers in the global South play a fundamental role in securing the long-term global food supply. Via their self-sufficient agricultural practices, they cultivate the crop genetic diversity that enables food crops to adapt to changing environmental conditions. In this paper I draw upon empirical data from the Guatemalan center of agricultural biodiversity to investigate the concern that market expansion will displace peasant agriculture and undermine a cornerstone of the global food supply. I find that even though peasants' livelihoods involve multiple forms of market provisioning, they also engage in a Polanyian 'double movement' to protect their subsistence-oriented agricultural practices from the potentially deleterious effects of markets. I also investigate the so-called 'agrarian question' about the effects of market expansion on the viability of peasant agriculture, finding that although new forms of market provisioning are likely exacerbating rural inequality, the income from market activities actually enables rural Guatemalans to reproduce the conditions for peasant agriculture. Ultimately, I observe that the conservation of agricultural biodiversity and, consequently, global food security are contingent upon the 'food sovereignty' of peasant farmers.
Keywords: Guatemala; agricultural biodiversity; agrobiodiversity; food crops; food industry; food sovereignty; food supply; globalization - social aspects; peasant differentiation; peasant livelihoods; peasant studies; peasants; right to food

‘Habitation vs. Improvement’ and a Polanyian Perspective on Bank Bail-outs - Watson, Matthew (Politics, 2009)
The bank bail-outs enacted by the Brown government in the wake of the 2007 credit crunch have had a distinctive political character. Despite the government's pronouncements on the merits of swift and decisive interventions, I argue that this does not amount to a return to the interventionist regulatory form associated with post-war British welfare capitalism. The Polanyian distinction between ‘habitation’ and ‘improvement’ is used to show that the bail-outs were designed by contrast to defend the underlying deregulatory logic of the existing financial regime. The only real change of note was to uncover forcibly the often hidden influence of the state in the making and regulation of an ostensibly market-led neoliberalism and the creation instead of a much more overt state-led neoliberalism. Habitation strategies were incorporated into a structure of financial deregulation, making it more rather than less difficult to rejuvenate state capacities consistent with enhancing societal welfare. The bank bail-outs offered short-term salvation for distressed firms within the financial sector without providing the state with socialised control over the conduct of banking business in order to promote forms of social policy consistent with post-war British welfare capitalism.
Keywords: BROWN, Gordon, 1951-; Great Britain; Great Britain - politics & government - 2007-; bailouts (finance); banking industry; habitation

Industrial Relations Today: Reining in Flexibility - Streeck, Wolfgang (Economics, Management & Financial Markets, 2009)
The paper was presented as a keynote lecture at the 10th anniversary of the Amsterdam Institute for Advanced Labour Studies (AIAS) in April 2008. It surveys the trajectory of scholarly work on labor after 1945, from its initial emphasis on rights of industrial and social citizenship to its present preoccupation with "flexibility" and "flexicurity." It recalls the dissolution of the "Fordist" compromise in the 1970s and the subsequent gradual expansion of markets as the dominant mechanism for the allocation of life chances and the governance of society. Marketization encountered surprisingly little resistance, in real life as in the evolving conceptual apparatus of scholarly work. Liberalization proceeded and continues to proceed regardless of the social dislocations it causes, on a scale wholly unimaginable and indeed unacceptable under the postwar settlement. The paper ends with speculation on what if at all might be the forces today that could trigger a Polanyian counter-movement to the progress of capitalist social and economic relations. In particular it discusses whether demographic change, in terms of both a declining birth rate and increasing life expectancy, might bring about a new wave of market-containing social policy.
Keywords: corporate growth; countermovement; industrial relations; international economic relations; labor laws & legislation; labour laws & legislation; socioeconomics; welfare economics

The Athenian Economy in Light of the Welfare State: Karl Polanyi's Work in Perspective - Wjuniski, Bernardo Stuhlberger; Fernández, Ramón García (Journal of Economic Issues (Taylor & Francis Ltd), 2009)
Karl Polanyi considered that the relationship between the markets and their societies was a central feature of any social order. He studied what he called "ancient societies," to compare them with his own times, in an effort to understand that subject This paper aims to show, following Polanyi's work on Classical Greece, that it is possible to make a clear analogy between the Athenian state and economy with the modern Welfare State. First, we present Polanyi's study of the early Athenian economy, focusing on the coexistence of a kind of state economic planning and a market Second, we show how this relates to Polanyi's emphasis in the comparison of different societies and times. Third, we characterize the contemporary Welfare State to make an analogy between these two forms of economic organization. We conclude by underlining the relevance of this analogy in understanding the societies of today.
Keywords: Athenian supremacy, Greece, 479-431 B.C.; Athens (Greece) - history; Greece; Polis (the Greek word); classical Greek economy; economic anthropology; economic policy; embeddedness; equity; history of economics - to 1800; imperialism; markets - social aspects; money; social order; welfare state

Challenging Neoliberalism in Latin America - Silva, Eduardo (Cambridge University Press, 2009)
At the turn of the twentieth century, a concatenation of diverse social movements arose unexpectedly in Latin America, culminating in massive anti-free market demonstrations. These events ushered in governments in Argentina, Bolivia, Ecuador, and Venezuela that advocated socialization and planning, challenging the consensus over neoliberal hegemony and the weakness of movements to oppose it. Eduardo Silva offers the first comprehensive comparative account of these extraordinary events, arguing that the shift was influenced by favorable political associational space, a reformist orientation to demands, economic crisis, and mechanisms that facilitated horizontal linkages among a wide variety of social movement organizations. His analysis applies Karl Polanyi's theory of the double movement of market society to these events, predicting the dawning of an era more supportive of government intervention in the economy and society.
Keywords: Latin America; double movement; market society; neoliberalism; political science / comparative politics; political science / world / general

Relaxing the shackles: The invisible pendulum - Stewart, Frances (Journal of International Development, 2009)
This note draws on Polanyi's pendulum in economic policies presented in the the Great Transformation—with swings back and forth between strong restrictions on the market and market domination, each resulting from excesses of the dominant model. The swing he described, when he wrote, was a reaction to the consequences of market domination, notably the Great Depression, and ushered in Keynesianism and the welfare state. In the late twentieth century, there was a swing back towards the market as a result of the inefficiencies associated with this interventionism. This note argues that the pendulum is swinging again, following the political and economic consequences of this market domination. Again market forces are being restrained by regulation, state takeovers, social protection and Keynesian macro-policies, while environmental factors have added to pressures for interventionist policies. Copyright © 2009 John Wiley & Sons, Ltd.
Keywords: Polanyi; interventionism; markets; pendulum

Headlong into the Polanyian Dilemma: The Impact of Middle-Class Moral Panic on the British Government's Response to the Sub-prime Crisis - Watson, Matthew (The British Journal of Politics & International Relations, 2009)
This article focuses on the discursive construction in Britain of a middle-class moral panic occasioned by the distress caused to self-styled ‘responsible mortgage borrowers’ by falling house prices. In the context of the move towards asset-based welfare the sub-prime crisis manifested itself most obviously in the popular consciousness as a threat to housing market wealth. The Labour government used the political space opened up by the narrative of middle-class moral panic in order to protect banks' balance sheets from the consequences of their own failed investments in mortgage-backed securities. The ensuing arrangements immunised banks from the implications of market self-regulation in the first-phase response to the sub-prime crisis while simultaneously allowing them to continue to impose the experience of market self-regulation on their customers. An increasingly asymmetric approach to banking regulation has arisen analogous to that which Karl Polanyi associated with the contradictory co-existence of market and non-market forms.
Keywords: market self-regulation; moral panic; protective re-embedding of finance; sub-prime crisis

Sociopolitical sustainability -- the pendulum at globalisation's frontiers - Boutilier, Robert (Keeping Good Companies (14447614), 2009)
The article explores the potential roots of the unsustainability of the intersectoral dynamic. Political economist Karl Polanyi stresses that excesses of globalisation led to the unsustainability among the private, public and civic sectors. The backlash against globalisation and the private sector has its roots in the imbalance among the three sectors. The impact of the absence of regulatory regimes on globalisation's frontiers on the private sector is discussed, as well the process by which companies help stabilise their partners.
Keywords: economic sectors; globalization; international relations; private sector; sustainability

Drivers of development over the next 30 years: Some speculations - Harriss, John (Journal of International Development, 2009)
Class relationships are amongst the fundamental drivers of development, and it is argued here that over the next 30 years a major influence on the pattern and path of development will be exerted by the rise of the ‘new middle classes’ of Asia. At the same time, in the context of the blocked transition of the present, it seems unlikely that those who are marginalised and excluded will be able adequately to organise resistance, much less change structures of power, but poverty will be managed through welfare interventions like India's National Rural Employment Guarantee Scheme. Copyright © 2009 John Wiley & Sons, Ltd.
Keywords: Asia; India; double movement; eastern hemisphere; economic development; middle class; new middle class; social change; social classes; social structure

Development's invisible hands: Introduction to special issue - Thomas, Alan; Sumner, Andy; Tribe, Michael (Journal of International Development, 2009)
This Special Issue comes from the Development Studies Association (DSA) 30th Anniversary conference in 2008. The theme was ‘Development's Invisible Hands’, focusing on the forces likely to influence global change and re-shape development agendas over the next 30 years. The first section comprises brief invited thinkpieces mainly from DSA past presidents. Interestingly, while some focus on Adam Smith's original ‘invisible hand’ analogy and others discuss a range of non-market issues, several invoke Karl Polanyi on the limitations of market society. The second and third sections consist, respectively, of ‘synthesis’ papers on parallel panel themes and papers developed from the best panel presentations. The papers demonstrate the range of issues raised by questioning the future of development and development studies—while the limitations of future gazing are pointed up by the unexpected challenge to current development models presented since the conference by the global financial crisis. Copyright © 2009 John Wiley & Sons, Ltd.
Keywords: Development Studies Association; POLANYI, Karl, 1886-1964; SMITH, Adam, 1723-1790 - political & social views; development economics; development studies; economic development; futures; invisible hand; mathematical models of economics

Polanyi in the United States: Peter Drucker, Karl Polanyi, and the Midcentury Critique of Economic Society - Immerwahr, Daniel (Journal of the History of Ideas, 2009)
Abstract:This essay explores the connections between Karl Polanyi's The Great Transformation (1944) and midcentury social theory in the United States. It argues that Polanyi shared with his U.S. colleagues a critique of market society. In particular, Polanyi's work bears close resemblance to the early thought of management theorist Peter Drucker, with whom Polanyi lived while writing his celebrated book. By comparing Polanyi to his contemporaries who advanced similar ideas, one gains a clearer sense of the particularities of Polanyi's project and of the fairly widespread movement in the United States to reject economistic thinking.
Keywords: DRUCKER, Peter; history; social theory

The unknown Karl Polanyi - Cangiani, Michele (International Review of Sociology, 2009)
Keywords: biography; essence of fascism

Subaltern strategies and autonomous community building: a critical analysis of the network organization of sustainable agriculture initiatives in Andhra Pradesh - Kumbamu, Ashok (Community Development Journal, 2009)
This paper examines and analyses the organization and functioning of subaltern peasant sanghams (grassroot associations of the poor) and their place-based as well as network-based strategies in building autonomous local communities that challenge the consequences of neoliberal globalization in general and the commodification of agriculture and food in particular. The major objective of the counter-hegemonic organizational strategies is to build self-protective and subsistence communities, to mend the metabolic rift between nature and society, and to re-reconstruct social fabric within communities. The question remains is whether place-based autonomous communities can sustain in an increasingly globalizing world. To better understand these political dynamics, I use Karl Polanyi's concept of ‘double movement’ and examine the making of a double movement in Indian agriculture and its socio-political and ecological implications for the Indian peasantry. I use the organizational strategies and activities of the Deccan Development Society, a prominent non-governmental organization that has been working in Medak district for more than two decades, as an illustrative case study.
Keywords: community development; community organizing; double movement; metabolic rift; peasant studies

Institutionalization of Trust as Response to Globalization: The Case of Consumer Cooperatives in South Korea - Choi, Hyejin (Transition Studies Review, 2009)
This paper explores an explanation which elaborates how individuals effectively enact and sustain trust in the sphere of social economy and the capability. I discuss how value employed by actors and the strategies and power relation in the socio-economic value sphere and focus on the function of ‘trust’ as the key mechanism of the interaction. This paper examine South Korean consumer cooperative Hansalim as a case of social economy which successfully institutionalize their system in competitive economic market arena.
Keywords: disembeddedness; double movement; embeddedness; food trust; governance; public administration; risk socety; social economy

The Extended Case Method: Four Countries, Four Decades, Four Great Transformations, and One Theoretical Tradition - Burawoy, Michael (University of California Press, 2009)
In this remarkable collection of essays, Michael Burawoy develops the extended case method by connecting his own experiences among workers of the world to the great transformations of the twentieth century—the rise and fall of the Soviet Union and its satellites, the reconstruction of U.S. capitalism, and the African transition to post-colonialism in Zambia. Burawoy's odyssey began in 1968 in the Zambian copper mines and proceeded to Chicago's South Side, where he worked as a machine operator and enjoyed a unique perspective on the stability of advanced capitalism. In the 1980s, this perspective was deepened by contrast with his work in diverse Hungarian factories. Surprised by the collapse of socialism in Hungary in 1989, he journeyed in 1991 to the Soviet Union, which by the end of the year had unexpectedly dissolved. He then spent the next decade studying how the working class survived the catastrophic collapse of the Soviet economy. These essays, presented with a perspective that has benefited from time and rich experience, offer ethnographers a theory and a method for developing novel understandings of epochal change.
Keywords: social science; sociology

Market and Society: The Great Transformation Today - Hann, Chris; Hart, Keith (Cambridge University Press, 2009)
Karl Polanyi's 1944 book, The Great Transformation, offered a radical critique of how the market system has affected society and humanity since the industrial revolution. This volume brings together contributions from distinguished scholars in economic anthropology, sociology and political economy to consider Polanyi's theories in the light of circumstances today, when the relationship between market and society has again become a focus of intense political and scientific debate. It demonstrates the relevance of Polanyi's ideas to various theoretical traditions in the social sciences and provides perspectives on topics such as money, risk, work and the family. The case studies present materials from around the world, including Britain, China, India, Jamaica and Nigeria. Like Polanyi's original work, the critical engagement of these essays will be of interest to a wide readership.
Keywords: anthropology - general; business & economics; economic history; economic theory; sociology - general

Karl Polanyi's Great Transformation and Development Politics - Deutschmann, Moritz (Grin Verlag, 2009)
English, abstract: Attempts to understand the transformation processes in the developing world have often led to a closer examination of Europe′s and America′s own history, as many theories of development suggest a specific interpretation of these histories: Modernization theorists, for example, see Europe′s and America′s history mainly as a straightforward progression towards welfare and democracy, eclipsing the aspects that do not fit into this picture, like the World Wars or the American Civil War. Therefore, although Karl Polanyi′s "The Great Transformation" treats mainly historical events in Europe, it can at the same time be an important contribution to our understanding of the economic and social transformations in the developing world. In this essay, I will first try to make clear, what assumptions underlie Polanyi′s argument and what he means by the notion of "market society." I will proceed in three steps: first, I will explore the different roles that the economy, according to Polanyi, plays in capitalist and pre-capitalist societies; I will look then at the historical processes that led to the rise of a "market society." Finally, I will discuss the political reactions to these processes which can be characterized, in Polanyi′s view, by a "double movement." As Polanyi is one of the most important critics of economic liberalism, it is helpful to compare his account of the "Great Transformation" to a second, even more influential anti-liberal perspective, Marxism. Apart from some similarities, the fundamental difference seems to be that Polanyi does not give a positive account of modernization. This leads to the question, how Polanyi′s theori
Keywords: Great Transformation, The (Book); development; double movement; market society; modernization

Exchange networks and free shops in Berlin: gifts and commodities in ‘alternative’ consumption experiences - Sabaté Muriel, Irene (Etnográfica. Revista do Centro em Rede de Investigação em Antropologia, 2009)
This paper is based on an ethnography of ‘alternative’ consumption practices in the inner city of the former East Berlin. Non-monetary exchange networks (Tauschringe) and ‘free shops’ (Umsonstläden) have been examined. In Umsonstläden, the contemporary ideology of the ‘pure’ gift (Parry 1986; Carrier 1995) is at play: objects are freely given and totally alienated from their owners. In turn, Tauschringe sometimes induce gift-giving practices entailing mutual obligation, as a result of frequent exchanges which bring participants socially closer. The ethnographic material I present challenges the suitability of a conceptual gift / commodity divide to examine these experiences, provided that different modalities of gift-giving are articulated with commoditisation trends. Considering this complexity, I propose a re-examination of the role of the gift in ‘alternative’ consumption practices promoted by social movements in Berlin., O artigo baseia-se numa etnografia de práticas de consumo “alternativas” nos bairros centrais da antiga Berlim-Leste. São aqui analisadas as redes de intercâmbio não monetário (Tauschringe) e as “lojas gratuitas” (Umsonstläden). As Umsonstläden são enquadradas pela ideologia contemporânea da dádiva “pura” (Parry 1986; Carrier 1995): os objectos são dados gratuitamente e totalmente alienados dos seus possuidores. Já as Tauschringe, por seu lado, induzem por vezes práticas de oferta que implicam obrigações mútuas, como consequência de trocas frequentes que aproximam socialmente os participantes. O material etnográfico apresentado põe em causa a adequação do binómio dádiva / mercadoria à análise dessas experiências, na medida em que diferentes modalidades de oferta se conjugam com tendências para a mercadorização. Face a essa complexidade, o artigo propõe uma revisão da análise do papel da dádiva em práticas de consumo “alternativas” promovidas pelos movimentos sociais em Berlim.
Keywords: Berlin; consumption; economic anthropology; embeddedness; exchange networks; fallacy of the market; free shops; gifts/commodities; social economy; social movements

Globalization and Backlash: Polanyi's Revenge? - Burgoon, Brian (Review of International Political Economy, 2009)
This paper investigates political-economic backlash to economic globalization in industrialized polities. It analyzes data on the content of party platforms to develop measures of party support for, or opposition to, political-economic closure, anti-democratic nationalism, and xenophobia in all party platforms of 23 Organization for Economic Cooperation and Development countries for all national elections between 1960 and 2003. These allow broader judgments of trends in autarky and autarchy than focusing on electoral success of particular extreme-right parties. Based on these measures, the paper quantitatively analyzes how international trade and capital openness and flows, and immigration flows, all influence the embrace or rejection of political-economic backlash among parties. The main explanatory finding is that immigration and capital flows and openness tend to increase marginally such backlash when national welfare compensation is very modest, but to reduce it when national compensation is generous, cushioning citizens from globalization's economic risks. This finding provides evidence that the current wave of globalization only marginally resembles the dark politics ending its nineteenth-century predecessor, and that welfare protection may help make the difference between political-economic backlash and liberalism in contemporary globalization.
Keywords: elections; international business; international economic order; international factor movements; legislatures; lobbying; political processes; rent-seeking; voting

Paper assets, real debts: An ecological‐economic exploration of the global economic crisis - Kallis, Giorgos; Martinez‐Alier, Joan; Norgaard, Richard B. (Critical perspectives on international business, 2009)
Purpose – This paper sets out to investigate the potential contribution of the inter‐disciplinary field of ecological economics to the explanation of the current economic crisis. The root of the crisis is the growing disjuncture between the real economy of production and the paper economy of finance. Design/methodology/approach – The authors trace the epistemological origins of this disjuncture to the myths of economism – a mix of academic, popular and political beliefs that served to explain, rationalise and perpetuate the current economic system. Findings – The authors recommend ending with economism and developing new collective and discursive processes for understanding and engaging with ecological‐economic systems. Originality/value – The authors embrace the notion of sustainable de‐growth: an equitable and democratic transition to a smaller economy with less production and consumption.
Keywords: commodification; commodification of nature

An Introduction to Destructive Coordination - Vahabi, Mehrdad (American Journal of Economics and Sociology, 2009)
Polanyi (1944, [1957]1968) has distinguished three “patterns of social integration,” namely, “reciprocity,”“redistribution,” and “exchange.” This triad has provided the starting point for most subsequent discussion. Our purpose is to introduce a further type of coordination, the “destructive mode of coordination.” This mode achieves coordination by intimidation, threat, and the use of non-institutionalized coercive means. Resources and human efforts are allocated in order to appropriate what other people produce. Two simple examples provide an introductory illustration: traffic circles (roundabouts) and prisons. Appropriation through pirating provides a further example of destructive coordination. More specifically, biopiracy (blood patenting) is discussed in order to clarify the relationship between destructive coordination and the institutionalization of property rights. Finally, we focus on the role of destructive coordination as a transitional mechanism that is supported by the institutional vacuum, ultimately yielding to other modes of coordination.
Keywords: appropriation; destructive mode of coordination; social integration

Karl Polanyi in Budapest: On his Political and Intellectual Formation - Dale, Gareth (European Journal of Sociology / Archives Européennes de Sociologie, 2009)
AbstractA major thinker and inspiring teacher, Karl Polanyi's contributions have long been influential in a variety of disciplines, notably economic sociology and economic history. Two of his innovations, substantivist economic anthropology and the “double movement thesis,” are recognized as seminal. All of the works for which he is known, however, were written late in life, when in exile, and very little is known of his Hungarian writings, virtually none of which had, until now, been translated. Despite his fame, the biographical literature on Polanyi remains modest: some studies provide invaluable insights, yet all are brief. This article attempts to make some headway in remedying these lacunae. It sketches the contours of that extraordinary historical-geographical conjuncture in which he was formed, and explores his intellectual and political engagements in the Galilei Circle and the Radical Bourgeois Party. It seeks in particular to elucidate the complex roles played by questions of nation, ethnicity and class in the life of the young Karl Polanyi.
Keywords: Hungary; Jewish assimilation; biography; liberal radicalism

The Social Economics of Neoliberal Globalization - Stanfield, James Ronald; Carroll, Michael C. (Forum for Social Economics, 2009)
The recent period of intensive and extensive development of global economic integration, or globalization, has reached a crossroads. The regime of the neoliberal Great Capitalist Restoration is not sustainable and fundamental governance changes must be made. This paper adds perspective to the choices that must be made at this critical juncture of the global social economy by applying the master concepts of Schumpeter's Creative Destruction and Polanyi's Protective Response.
Keywords: capitalist systems: political economy; global social economy; international economic order; protective response; social economy

Economics, Anthropological Models and the Ancient Near East - Warburton, David A. (Anthropology of the Middle East, 2009)
This article discusses the evidence of markets in the Ancient Near East. The major points are (1) the shortcomings of the misguided application of the Polanyi model and (2) the ensuing implications of the failure to integrate economic history into modern economic theory. The analysis concentrates on Ancient Egypt, as it presents the most significant problem for economic history and theoretical modelling. Detailed criticism of the means by which the Polanyi model is upheld is coordinated with an argument in favour of recognising the importance of markets. The argument is that these markets are relevant both to long-term economic history and to modern economic theory – and that this must lead to a new debate about ancient and modern economies.
Keywords: Egypt; Middle East; ancient civilization; anthropology; economic history; economic theory; economics; markets; neo-classical synthesis; technology

Why Karl Polanyi Still Matters - Bollier, David (On the Commons, 2009)
It's a ripe moment to dust off "The Great Transformation" and its anthropological critique of "self-regulating markets."
Keywords: commons

Precarious Work, Insecure Workers: Employment Relations in Transition - Kalleberg, Arne L. (American Sociological Review, 2009)
The growth of precarious work since the 1970s has emerged as a core contemporary concern within politics, in the media, and among researchers. Uncertain and unpredictable work contrasts with the relative security that characterized the three decades following World War II. Precarious work constitutes a global challenge that has a wide range of consequences cutting across many areas of concern to sociologists. Hence, it is increasingly important to understand the new workplace arrangements that generate precarious work and worker insecurity. A focus on employment relations forms the foundation of theories of the institutions and structures that generate precarious work and the cultural and individual factors that influence people's responses to uncertainty. Sociologists are well-positioned to explain, offer insight, and provide input into public policy about such changes and the state of contemporary employment relations.
Keywords: precarious work; precarity

Embeddedness of Social and Economic Relations in Systemic Transformation. Long-Term Evidence From the Post-Communist Transition in Poland, 1988-2003 - Wilk, Katarzyna (Polish Sociological Review, 2009)
This paper intervenes in the Granovetter-Polanyi debate by reassessing the level of embeddedness of social and economic relations under conditions of systemic transition. Using panel data collected in Poland, this analysis examines this relationship for three distinct periods of transition: initial (1988-1993), advanced (1993-1998), and post-transitional (1998-2003). This paper shows that during transition from communism to capitalism economic relations tended to disembed from social relations, but this relationship remained significant; friendship ties were conductive to an individual upward mobility, economic well-being and entrepreneurial activity. In contrast to Polanyi's argument, however, entrepreneurship—the most marketable area of individual advancement—is found to exhibit the highest degree of social-economic embeddedness. These results do not directly support either Polanyi's or Granovetter's arguments, however they do accord with a neo-Polanyian argument, as advanced in this paper.
Keywords: (dis)embeddedness; Poland; capitalism; disembeddedness; embeddedness; entrepreneurship; friendship ties; political doctrines; practical politics; social classes; social networks; social status; socioeconomics; status attainment

Towards a Green Republicanism: Constitutionalism, Political Economy, and the Green State - Barry, John (The Good Society, 2009)
In lieu of an abstract, here is a brief excerpt of the content: Towards a Green Republicanism: Constitutionalism, Political Economy, and the Green State John Barry (bio) The republic is threatened—who will stand by the republic? Introduction The range of threats to modern society ranging from growing environmental stresses (water shortages, deforestation, soil erosion to climate change), food and energy insecurity, peak oil, rising poverty and inequalities within and between societies, increasing passivity of citizens within democracies and the inexorable rise of corporate power within and over the democratic state can be summed up as facets of 'unsustainability' or 'unsustainable development.' Just as it is commonplace to declare that the 21st century will be China's century, equally the politics of the 21st century are and will be the politics of sustain-ability. Taking it as given that the transition to sustainability will be the dominant challenge and opportunity facing all societies in the coming decades ahead, this article looks at two traditions of political thought—namely green political theory and civic republicanism—and seeks to conjoin them to outline a new political approach—'green republicanism'—which may respond and rise to this challenge. It needs to be pointed out from the outset that what is discussed below is 'green politics' and not 'environmentalism,' which is narrowly concerned with environmental preservation, species conservation or combating climate change. In broad terms green politics aims at 'sustainable development' which, inter alia, deals with securing basic human rights, lowering socio-economic inequalities, eradicating environmental injustices (within nation-states and globally as well as intergenerationally) and ensuring the demands of the human economy do not outstrip the regenerative capacities of the eco-systems upon which that economy depends. Sustainable development therefore is a radical proposal, indicating not simply the 'ecologising' or 'greening' of the current political and economic order. Such reformist proposals may be viewed as interim staging posts such as those represented by 'ecological modernisation' and discourses of 'natural capitalism,' but suggest the transformation to a different distinctly 'green' or 'sustainable' political order.1 While the metabolism between the human economy and its ecological systems is the most pressing and significant [End Page 3] dimension of sustainable development, questions of political economy and the economic order are always already present in any green analysis (whether explicit or not). In the same way that I take it as given that a sustainable society is one that is a post-carbon society (in terms of energy production and consumption), the green republican perspective offered here is also one which sees such a society as post-liberal, though not anti-liberal. Green politics can be viewed as 'post' not 'anti-liberal' in Robyn Eckersley's terms, and this can be seen to settle around the centrality of separating free market capitalism as the dominant organization of the economy, from liberalism (representative democratic governance, citizen freedoms, equality of citizens, etc.) in the creation of a sustainable society.2 In short, a green republicanism is one which asks the question 'How do we maintain and sustain liberty in a post-liberal political, post-capitalist economic and post-carbon, sustainable order?' In that context it is important to look at what are the political and institutional dynamics within, between and below the nation-state of this transformation away from current unsustainable development paths. If we are to live in a sustainable/green political order different than the current liberal democratic one based on the capitalist free market, what are the types of legal, constitutional and institutional innovations we might expect to see in a greening state or in a fully fledged 'green state?' Thus, while this article is critical of reformist ecological modernisation and strategies that focus on securing (often through technological innovation) the ecological conditions for the political economy of expansionist fossil-fuelled capitalism, it is also critical of radical green proposals (mostly anarchistic in character) which argue for the eradication or transcendence of the nation-state as a necessary condition of achieving sustainable development. Thus, the position outlined here is firmly within that school of green political thought which is concerned about the evolution and emergence of green states and pragmatic/strategic considerations about the 'greening' of existing liberal democratic states. Green Constitutionalism Given that constitutional provisions...
Keywords: embeddedness; green republicanism; political economy

Informal Politics, Formalised Law and the ‘Social Deficit’ of European Integration: Reflections after the Judgments of the ECJ in Viking and Laval - Joerges, Christian; Rödl, Florian (European Law Journal, 2009)
The judgments of the European Court of Justice (ECJ) of December 2008 in Viking and Laval on the compatibility of national collective labour law with European prerogatives have caused quite a heated critical debate. This article seeks to put this debate in constitutional perspectives. In its first part, it reconstructs in legal categories what Fritz W. Scharpf has characterised as a decoupling of economic integration from the various welfare traditions of the Member States. European constitutionalism, it is submitted, is bound to respond to this problématique. The second part develops a perspective within which such a response can be found. That perspective is a supranational European conflict of laws which seeks to realise what the draft Constitutional Treaty had called the ‘motto of the union’: unitas in pluralitate. Within that framework, the third part analyses two seemingly contradictory trends, namely, first, albeit very briefly, the turn to ‘soft’ modes of governance in the realm of social policy and then, in much greater detail, the ECJ's ‘hard’ interpretations of the supremacy of European freedoms and its strict interpretation of pertinent secondary legislation. The conflict-of-laws approach would suggest a greater respect for national autonomy, in particular, in view of the limited EU competences in the field of labour law.
Keywords: BLOCK, Fred; European Union; European constitutionalism; economic law; labour law; social embeddedness

Who is right about the modern economy: Polanyi, Zelizer, or both? - Steiner, Philippe (Theory and Society, 2009)
Zelizer’s work may be read as an attack on the central Polanyian thesis: that the market system threatens social life by the undue prominence it lends the economy in the organization of modern society. The recent publication of Viviana Zelizer’s The Purchase of Intimacy (2005a) is therefore an excellent opportunity to review the general trend of her work Zelizer 1979, 1985, 1994, and contrast her leading ideas to the central thesis that gives Polanyi’s work its particular flavor: the danger encapsulated in the use of modern money and the functioning of the market system.
Keywords: ZELIZER, Viviana; market system; money

Beyond Social Democracy? - Gare, Arran (International Journal of Inclusive Democracy, 2009)
Towards an Inclusive Democracy, it is argued, offers a powerful new interpretation of the history and destructive dynamics of the market and provides an inspiring new vision of the future in place of both neo-liberalism and existing forms of socialism. It is shown how this work synthesizes and develops Karl Polanyi's characterization of the relationship between society and the market and Cornelius Castoriadis' philosophy of autonomy. A central component of Fotopoulos' argument is that social democracy can provide no answer to neo-liberalism, so the only viable alternative to neo-liberalism is the form of inclusive democracy he elaborates. Reviewing Castoriadis' concept of autonomy, it is argued that while Fotopoulos is certainly correct given the present deformed nature of social democracy, there is no reason to exclude social democracy as such from what Fotopoulos calls the tradition of autonomy. It is suggested that if the working class movement could free itself from the capitalist imaginary and return to its quest for autonomy, a synthesis of a radically reformed social democracy and inclusive democracy could greatly improve the prospects of each to successfully challenge not only neo-liberalism, but also the emerging liberal fascism of USA, Britain and Australia.
Keywords: CASTORIADIS, Cornelius, 1922-1997; democracy; fascism; neoliberalism; political doctrines; political science - study & teaching; review; social democracy; social movements; socialism

Polanyi and the Instituted Processes of Markets: Introducing a Wellbeing Perspective - Johnson, Susan (2009)
Analysis of the role of markets in development is mainly focused on their ability to promote material provisioning. Polanyi argued that markets were only one approach to material provisioning, and that the concept of the self-regulating market had become disembedded from society. He was concerned that processes of provisioning be understood within the wider framework of society and developed the concept of instituted process as a means to understand this role. This paper sets out to explore whether and how Polanyi’s concept of instituted process might work with emerging approaches to analysing wellbeing – what it means to live well – to offer tools for the institutional analysis of markets.
Keywords: embeddedness; instituted economic process; instituted process; institutions; well-being

Keynes’s Stimulus, Polanyi’s Movement - Milberg, William S. (Harvard College Economic Review, 2009)
The foundations of Keynes and the principles of Polanyi offer insight into crafting a new American economy
Keywords: KEYNES, John Maynard, 1883-1946; economics

The Financialization of Modern Economies in Monetary Circuit Theory - Pilkington, Marc (The Political Economy of Monetary Circuits: Tradition and Change in Post-Keynesian Economics, 2009)
Keywords: Canada: 1913-; banks; depository institutions; economic history: financial markets and institutions: United States; government and the monetary system; haute finance; history of economic thought: individuals; household saving; international financial markets; micro finance institutions; monetary policy, central banking, and the supply of money and credit; monetary systems; mortgages; payment systems; personal finance; regimes; standards

Second thoughts: on economics, sociology, neoliberalism, Polanyi's double movement and intellectual vacuums - Piore, Michael J. (Socio-Economic Review;2009, Vol. 7 Issue 1, p161, 2009)
The article presents a presidential address by Michael J. Piore, delivered at the Society for the Advancement of Socio-Economics (SASE) Annual Meeting 2008 in San José, Costa Rica, in which he discussed the relationship between sociology and economics, and the role that this relationship plays at the current political juncture in the transition from neoliberalism to the formation of public policy.
Keywords: double movement; economic sociology; neoliberalism

The Great Transition - Spratt, Stephen; Simms, Andrew; Neitzert, Eva; Collins, Josh-Ryan (New Economics Foundation, 2009)
Maps out a set of solutions to various systemic problems "This report argues that nothing short of a Great Transition to a new economy is necessary and desirable, and also possible. " - We have called the process by which this could happen the Great Transition as a deliberate echo of The Great Transformation, written by Karl Polanyi in the 1940s.1 While in a relatively short report such as this we could not hope to achieve anything remotely comparable to Polanyi’s great work, the scale of the change we need to see is at least the equal of the changes he described. Polanyi analysed how market processes in the industrial revolution had created severe ruptures in the fabric of social life, and argued strongly that we needed to reverse this and nd a balance between the market and the non-market; the private and the public; the individual and the community. We couldn’t agree more, and the need to achieve this is all the more pressing now given the huge environmental problems we face, problems that Polanyi could not have foreseen in 1944 when the world was caught in the bloody conclusions of the Second World War. The most pressing problem facing humanity now is how to share scarce planetary resources in ways that are just, sustainable and support the well-being of us all.
Keywords: environemntal politics; environmental value; redistribution

Human Rights and Business Practices: Double Movement or Neoliberal Hegemony? - Thomas, Mark (Conference Papers -- American Sociological Association, 2009)
Throughout the 1990s and into the early years of the 21st century, campaigns by labor rights activists brought the issue of labor exploitation by Northern transnationals (TNCs) operating in the Global South into the centre of public debate. Labor rights scholars raised the possibility of a broader Polanyian 'double movement' in the global economy, as the polarizing effects of neoliberal globalization produced anti-globalization movements and shifts towards forms of social protection through emerging approaches to transnational labor rights regulation. One of the results of these processes was the adoption of a human rights discourse by TNCs as they sought to re-define their public image in response to growing public awareness and condemnation of sweatshop labor practices. Read through a Polanyian lens, these developments would seem to confirm that a double movement was in fact producing a more socially responsible capitalism where the 'satanic mill' of the sweatshop would be moderated through corporations proclaiming respect for human rights. In this paper, I examine the adoption of human rights principles by corporate actors as both normative framework and business practice. I argue that rather than a double movement from market liberalism to social protection, the dynamics present in this process indicate tendencies towards the construction of a new hegemonic discourse to support neoliberal globalization - that of the 'socially responsible' corporation where business practices and human rights principles intersect. ..PAT.-Unpublished Manuscript
Keywords: employee rights; hegemony; human rights; neoliberalism; satanic mill; transnationalism

Markets Against Society: Labor's Predicament in the Second Great Transformation - Webster, Edward; Lambert, Robert (The ISA Handbook in Contemporary Sociology: Conflict, Competition, Cooperation, 2009)
Keywords: labour movement; northern compromise; second great transformation